2013
DOI: 10.1016/j.clay.2013.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hectorites, synthesized in different conditions, as soot combustion catalysts after impregnation with copper

Abstract: Two microporous hectorites were prepared by conventional and microwave heating, and a delaminated mesoporous hectorite by an ultrasound-assisted synthesis, and these three hectorites were impregnated with copper. The characterization techniques used were XRD, N 2 adsorption, TEM and H 2 reduction after selective surface copper oxidation by N 2 O (to determine copper dispersion). The catalytic activity for soot combustion of both the copper-free and the copper-containing hectorites was tested under a gas mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Hectorite (HEC) (Fig. 2e 220 Sinha Ray and Okamoto reported a CEC of $120 meq per 100 g. 17 A more recent study reported a CEC of 43.9 meq per 100 g, a surface area of $65 m 2 g À1 and basal spacing of 14.4 Å for Ca 2+ -HEC. 66 Other research conrmed a surface area of 63 m 2 g À1 .…”
Section: Inorganic Llers: Physicochemical Properties and Main Develo...mentioning
confidence: 99%
“…Hectorite (HEC) (Fig. 2e 220 Sinha Ray and Okamoto reported a CEC of $120 meq per 100 g. 17 A more recent study reported a CEC of 43.9 meq per 100 g, a surface area of $65 m 2 g À1 and basal spacing of 14.4 Å for Ca 2+ -HEC. 66 Other research conrmed a surface area of 63 m 2 g À1 .…”
Section: Inorganic Llers: Physicochemical Properties and Main Develo...mentioning
confidence: 99%
“…Microwaves have also improved the occupation of Al in the tetrahedral positions and delamination. In a previous study, 19 Cu/hectorite catalysts were prepared and tested for soot combustion, and in spite of their activity, their performance was still far away from being competitive for a practical use. 3 Delaminated mesoporous hectorites have been prepared by in situ hydrothermal aging of a polyvinylpyrrolidone-containing gel 4 or quaternary ammonium salt 5,6 followed by removal of the template by calcination.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a lot of investigation results have shown that interactions between each component of the supported metal-oxide catalyst can be adjusted by many factors, which results in different catalytic performances. [30][31][32][33][34][35][36] These influencing factors mainly include:…”
Section: Introductionmentioning
confidence: 99%